Clinical Outcomes of Patients with Atrial Fibrillation who Survived from Bleeding Event: The Results from COOL-AF Thailand Registry - Winijkul, Arjbordin; Kaewkumdee, Pontawee; Yindeengam, Ahthit; Lip, Gregory Y.H.; Krittayaphong, Rungroj (Thrombosis and Haemostasis, 2024)
Background Bleeding events are often reported among patients with atrial fibrillation (AF), irrespective of antithrombotic use. This study is to determine clinical outcomes of patients with AF who survived from bleeding event.Methods We analyzed data from COOL-AF (Cohort of Antithrombotic Use and Optimal International Normalized Ratio Levels in Patients with Atrial Fibrillation) Thailand registry. Outcomes of patients who experienced any bleeding were compared with patients who had never bleed. Time updated multivariate Cox-proportional hazard models were used to estimate the risk for clinical outcomes of patients with and without bleeding.Results Of total 3,405 patients (mean age: 67.8 ± 11.3 years; 41.9% female) in COOL-AF registry, 609 patients (17.9%) reported bleeding event occurs and 568 patients (93.3%) survived though hospital discharge. Patients who survived major bleeding (n = 126) were at increased risk for both death (adjusted hazard ratio [HR]: 4.44, 95% confidence interval [CI]: 2.91–6.75, p < 0.001) and stroke/systemic embolism (adjusted HR: 4.49, 95% CI: 2.19–9.24, p < 0.001). Minor bleeding also increased subsequent death (adjusted HR: 2.13, 95% CI: 1.56–2.90, p < 0.001). Up to 30% of patients who survived major bleeding and 6.3% of minor bleedings discontinued oral anticoagulation. Discontinuation was associated with very high death rate (42.1%), whereas patients who resumed oral anticoagulation after bleeding had lower mortality (10%). The most common causes of death in patients who survived a bleeding event were not related to cardiovascular causes nor bleeding.Conclusion Patients with AF who have bleeding events have an increased risk for subsequent death and stroke and systemic embolism. These patients should be identified as vulnerable clinically complex patients and require a holistic approach to their AF management.
Keywords: atrial fibrillation; bleeding; death; oral anticoagulants